Understanding Learners’ Difficulties with English Plural –S: The Role of Phonological Interference - Riskiana, Riskiana; Aristiyanto, Roma (Universitas Stikubank (UNISBANK) Semarang, 2026)
Abstract This study investigated learners’ difficulties in pronouncing the English plural –s and examines the role of phonological interference in shaping these difficulties. The research focuses on PGMI students, who often experience challenges in producing the correct plural endings, potentially leading to miscommunication. Using a qualitative descriptive approach, data were collected from 40 students through recordings of their reading of 20 sentences containing plural nouns. The data were analyzed by transcribing students’ pronunciations into phonetic symbols, classifying pronunciation errors, and identifying patterns of phonological interference from Indonesian. The findings reveal that out of 800 pronunciation instances, 327 (41%) were correct, while 473 (59%) were incorrect. The errors fall into four main categories: omission of the –s suffix, substitution of /s/ for /z/, substitution of /ɪs/ for /ɪz/, and substitution of /əs/ for /z/. These results suggest that differences between Indonesian and English phonological systems significantly influence learners’ pronunciation of the plural –s marker. Keywords: English plural –s, pronunciation difficulties, phonological interference, EFL learners